Emergence of Lava Dome from the Crater Lake of Kelud Volcano, East Java - Hidayati, Sri; Basuki, Ahmad; Kristianto, Kristianto; Mulyana, Iyan (Indonesian Journal on Geoscience, 2009)
DOI:Â 10.17014/ijog.v4i4.83Kelud Volcano (+1731 m) in East Java is one of the most active and dangerous volcanoes in Indonesia. A large lake occupies the summit crater. Historical eruptions generally only lasted for a very short time, mostly no longer than a few hours. The outburst is usually accompanied by pyroclastic flows. On August 2007, the activity of the volcano was initiated by the increase of the temperature of lake water and the change of the colour from typical green to yellow. Activities of the volcano are discussed following the swarms of volcano-tectonic (VT) earthquakes on September 10th, September 26th to 29th, and October 24th to November 2nd. On September 26th to 29th, hypocentral distribution of those VT shifted from 5 km deep to just beneath the crater. The highest number of VT earthquakes occurred on November 1st attaining 50 events, then followed by a swarm of B-type events, where the number reached 1437 events in a day. The volcanic activity peaked on November 3rd when seismic records became saturated, which then was preceded by a sharp increase of lake temperature and a sudden deflation of radial tilt. It suggests that the lava extrusion forming a lava dome was taking place.